Stealth democracy : Americans' beliefs about how government should work - Hibbing, John R. (Cambridge studies in political psychology and public opinion., 2002)
"Americans often complain about the current operation of their government, but scholars have never developed a complete picture of people's preferred type of government. In this provocative and timely book, John Hibbing and Elizabeth Theiss-Morse, employing an original national survey and focus groups, report the specific governmental procedures Americans desire. Their results are surprising. Contrary to the prevailing view that people want greater involvement in politics, most citizens do not care about most policies and therefore are content to turn over decision-making authority to someone else